THE CONTENT OF INTERLEUKINS IN ORAL FLUID OF PATIENTS WITH NON-REMOVABLE METAL CERAMIC PROSTHESES - Yu. M. Hotsko; L. Ye. Lapovets (Ukrainian Medical Stomatological Academy, 2018)
The dental bridges are often used to replace missing teeth. Currently, the most common are the metal-ceramic structures, which have the high mechanical properties and are aesthetic and functional, because they restore chewing efficiency by 85-100% and provide a high level of adaptation to them. However, in the presence of metallic and combined prostheses in the oral cavity, the pathological changes may occur, taking into account that in the oral cavity, the non-removable dentures are foriegn bodies affecting the tissues and the environment of the oral cavity. The effect of almost all artificial bridges on the tissues of the marginal periodontal disease depends on the level of the location of the bridge margin and the depth of the immersion under the gum. In the presence of such processes, the main factor is the specific antimicrobial protection, which is carried out by immunoglobulins; in the oral cavity, there are present only IgA, IgG, IgM of six classes. Thus, in the prosthetic dentistry one of the important problems is the connection of prosthetic constructions and the state of the oral cavity - homeostasis. The dental prostheses activate the lipid peroxidation and reduce the antioxidant defense factors. On the 7th day after bridge fixation, there is a significant decrease in the level of antioxidant enzymes and immunoglobulins and high concentrations of anti-inflammatory cytokines and interleukins. It is found that on the first stage of dental prosthesis the activity of lysozyme is sharply reduced and then restored very slowly. There is reduced not only non-specific reactivity (lysozyme), but also specific (lgA, IgG, and IgE) affected by dental prostheses, in particular, from acrylic plastics. The clinical data of 46 patients, age between 29 - 73 years old (56% of women, 44% of men), which had the non-removable metal ceramic crowns and bridge prostheses, and the indicators of immune markers in the oral fluid were used. In a determination of IL-1β concentration in the saliva of the tested patients, there was found a significant increase by a factor of 12 in the control parameters, it indicates on the high activity of the monocyte-macrophage lineage cells. In the saliva, the increased content of IL-1β confirms its role in the local inflammatory process and indicates the activation of endothelial cells and connective tissue. In the group of patients, IL-6 salivary content exceeds the level in healthy people by 3.66 times, indicating a protective mechanism that is necessary for the initial phase of inflammation. The IL-6 high level is a prognostic adverse factor, which can indicate the progression of the inflammatory process and the increase of membrane-destructive disorders in the cells. Monocytes and macrophages, activated by periodontopathogenic microbes, produce all cascade of proinflammatory interleukins, causing an imbalance between them. The damage of the periodontal tissue and resorption of the alveolar bone occur. In periodontal disease, the most damaging effect is characteristic for IL-1β and TNF-α. In the saliva of patients, there was detected an increased TNF-α level by 2.89 times compared to control, that has a negative inotropic effect, stimulates apoptosis, and increases vascular wall permeability. In prolonged prosthesis in the saliva of patients, there was found the higher level of IL-4 than in healthy individuals by 1.24 times. IL-4 is an anti-inflammatory cytokine, an activator and chemokinetic factor for phagocytes. The cytokines ensure the consistency and completeness of the immune response. Most of them induce inflammatory reaction and acute phase response of the organism and can exhibit the immunopathological effect on the tissues. At the systemic level, cytokines modulate the key protective reactions of the organism.